Repertórios léxicos hispano-lusos en los manuales de conversación - Díaz de Durana, Nerea Fernández de Gobeo (Linguarum Arena, 2019)
This paper examines the lexical repertoires in Spanish and Portuguese that are included in two conversation manuals: O espanhol tal qual se fala. Novissima guía de conversação com a pronúncia figura, work elaborated for the Portuguese who want to learn Spanish; and the Manual de la conversación y del estilo epistolar, for the acquisition of Portuguese by Spaniards. The vocabularies inserted in both works are thematically grouped: they constitute nomenclatures, repertoires that are very common within the tradition of teaching and learning foreign languages. In addition, these vocabularies are complemented with a column dedicated to the pronunciation of the target language, in a similar way to other contemporaneous texts. Therefore, the analysed works are not original, but they are a good sample of the materials used throughout the history of foreign language teaching.